Correlation of Plasma Cell Percentage and Monoclonal Gammapathies with Biochemical Parameters in Multiple Myeloma Patients: A Retrospective Study - R Sindhu, Edakkadath; Das, Aptha Y; Padmanabhan, Maya; K Nair, Chandran (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Multiple myeloma is characterized by the uncontrolled proliferation of monoclonal plasma cells in the bone marrow, leading to the production of non-functional intact immunoglobulin chains. This retrospective study aimed to investigate the correlation between plasma cell percentage (below 60% and above 60%) in different types of monoclonal gammapathies (IgA, IgG) and various biochemical parameters. Materials and Methods: This analysis was conducted at the Division of Biochemistry in the Malabar Cancer Centre, a tertiary care cancer center in Kerala, India. A total of 89 patient case reports were reviewed, with complete treatment data available for 60 patients. The study evaluated the relationship between plasma cell percentage (below 60% and above 60%) in different types of monoclonal gammapathies (IgA, IgG) and various biochemical parameters. Results: The majority of patients enrolled in the study were over 60 years of age, with more men than women included. Among the studied parameters, a significant increase in plasma protein level was observed in the group with a plasma cell percentage below 60% and IgG type monoclonal gammopathy (P value = 0.014, p < 0.05). Additionally, a significant elevation in WBC count was observed in patients with a plasma cell percentage below 60% and IgG type MM compared to IgA type MM patients (p = 0.023, p < 0.05). However, no significant changes were observed in plasma protein level, liver enzyme activity, renal function, serum electrolytes, CBC, and calcium level between patients with plasma cell percentages above and below 60% in multiple myeloma. Conclusion: This study found that only a few biochemical and hematological parameters showed significant deviations between plasma cell percentages above and below 60% in different types of monoclonal gammapathies in multiple myeloma patients.